DISTRIBUSI DAN MARGIN PEMASARAN HASIL TANGKAPAN IKAN DI TPI PANTERAJA - Nadilla; Agus Naufal; Faisal Syahputra (Lembaga Riset dan Inovasi Kreyat Center, 2025)
The purpose of this research is to know Catch distribution pattern in TPI Panteraja and its marketing margin. This research method uses survey method in the field which is direct data collection to respondents. The technique of collecting resource persons uses survey and interview method with Snowball technique. Survey and interview using Snowball technique. The type of data collected is primary data. The result of this research in TPI Panteraja has two distribution patterns. Distribution pattern. Pattern 1 consists of fishermen, collecting traders, juragan, consumers. While Pattern 2 consists of fishermen, bench toke, Medan. And the highest marketing margin in pattern 1 at toke bench is found in anchovies with the highest marketing margin in pattern 2. The highest margin in pattern 1 at toke bench is found in anchovies with a margin value of 29.375 and the highest margin in pattern 1 at muge is found in anchovies. The highest margin in pattern 1 in muge is in the type of belaling fish with a margin value of 12,000. While the highest marketing margin in pattern 2 at the toke bench is in the anchovy type with a margin value of 55,000. anchovy with a margin value of 55,750, and the lowest in the type of anchovy with a margin value of 3,000. The highest marketing margin in pattern 2 on the toke bench is found in the type of fish petek fish with a margin value of 3,000.